Application of solar panels in IoT-based bird pest control tools - Fitri Harahap; Nazaruddin Nasution; Mulkan Iskandar Nasution (Indonesian Physics Communication, 2024)
The use of solar panels in bird pest control equipment in the rice field zone is based on the internet of things (IoT), which aims to create bird pest control equipment for farmers. This control system is equipped with a PIR sensor whose role is to determine the presence of birds in the rice field zone. The distance range when a bird is found is 5 meters, and an ultrasonic speaker will be active when there is bird movement in the rice field. This speaker uses an ultrasonic wave frequency of 20 kHz. RTC testing is used as a timer to reset the number of invasions in 1 × 24-hour intervals at 00.00 WIB. Next, there is a test of sending (transmitter) and receiving (receiver) LoRa material information near ± 450 meters, information to be sent and placed on the dashboard things board.